THE IMPACT OF HUMAN - NATURE INTERACTIONON THE ENVIRONMENT:AN ECOCRITIC ANALYSIS IN SELECTED SHORT STORIESFROM PIKIRAN RAKYAT - Citra Desianti, - (2009)
Entitled The Impact of Human - Nature Interaction on the Environment (An Ecocritic Analysis in Selected Short Stories from Pikiran Rakyat), the present paper concerns a textual analysis of selected short stories from Pikiran Rakyat daily newspaper, in an ecocritical framework with the employment of the ecocriticism theory with regards to the impact of human-nature interaction. The analysis is directed to unveil the impact of human-nature interaction in relation to human life survival as it is presented in the text. Based on the findings, it is revealed that there are two kinds of human-nature interactions; homocentric or anthropocentric with human as the center of the interaction and ecocectric with nature as the center of the interaction. The analysis also proves that what is often called as "natural disaster" is best called as "human disaster" because the reasons of why the disaster happens are man-made. Subsequently, as the findings show that the analyzed texts can be considered as "Ecocritcal Writing" and are classified as "Green Literature", the analysis had successfully proved that literature has potential to encourage people awareness about the environmental and natural preservation through profound ecological implication delivered in the literary texts.